Evaluation of Land Use Potential for Nipa Palm Using Geographic Information System: A Case Study of Wang Won Sub-District, Kan Tang District, Trang Province - Saravisutra, Apiradee; Taksinsampan, Supannee; Sowana, Akom; Tansupol, Anukul; Siammai, Damrong (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2021)
The purposes of this research were: 1) to analyze land suitability for Nipa Palm and 2) to assess land potential for Nipa Palm through a comparison of suitable areas with the land use in 2019. The evaluation process went through three phases: 1) 60 samples were analyzed by statistical methods for selecting significant factors and creating a logistic regression model; 2) each value was substituted in the logistic regression model for analyzing suitable areas for Nipa Palm; and 3) comparison of land suitability with land use in 2019 was conducted for assessment of potential areas for Nipa Palm. The results showed 5 significant factors: geomorphology, soil depth, soil drainage, soil reaction and river buffer. The analysis of the geographic information system was 12.96 km2 of area potential. Compare suitable areas with landuse 2019 that is visually interpreted. Further results showed that the most potential areas were those for miscellaneous uses and less than 200 meters from the river buffer zone (0.58 km2). These areas were Ban Laem village and Ban Klang village, located in the middle of the study areas.